2005
DOI: 10.1002/anie.200463084
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Hyperfine Interaction in the Manganese(III) Hexaaqua Ion

Abstract: The manganese(iii) ion is ubiquitous among chemical systems that exhibit intriguing biological and physical properties, ranging from photosystem II and superoxide dismutase to the celebrated single-molecule magnet Mn 12 . It is for this reason that complexes and clusters of the manganese(iii) ion are widely recognized as the delicicae of high-field electron paramagnetic resonance (EPR) spectroscopists, [1] the fact that they invariably yield good-quality spectra being but a secondary consideration. [2][3][4][5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
36
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 14 publications
6
36
0
1
Order By: Relevance
“…In comparison with literature values for each respective oxidation state, the present values are within the observed ranges of isotropic hyperfine constants for Mn. 20,34,35,4446 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with literature values for each respective oxidation state, the present values are within the observed ranges of isotropic hyperfine constants for Mn. 20,34,35,4446 …”
Section: Resultsmentioning
confidence: 99%
“…This causes mixing of spin states and multiple overlapping transitions, and consequently, the interpretation of spectra has been qualitative. High-field EPR studies on monomeric Mn II and Mn II have been reported in literature, which can give more accurate determinations of g - and D -values 1620 . We have developed a methodology for quantitative interpretation based on computer simulation of spectra, and here we demonstrate its use in the interpretation of X- and Q-band spectra for both parallel ( B 1 ‖ B ) and perpendicular ( B 1 ⊥ B ) orientations of the oscillating microwave field ( B 1 ) relative to the static field ( B ) 21 .…”
Section: Introductionmentioning
confidence: 99%
“…6 Among the most appropriate techniques for studying high-spin (HS) manganese(III) complexes is high-frequency and -field EPR spectroscopy (HFEPR), first of all because this spin system usually produces good-quality spectra. 7 In addition, although HS manganese(III) systems can also produce X-band EPR spectra, 8 extraction of spin Hamiltonian parameters such as the Landé g factor, the magnitude and sign of the axial anisotropy parameter, D, the presence of rhombic anisotropy, E, and fourth order spin Hamiltonian terms is not always possible. 9 The magnitude and sign of the anisotropy, however, can provide information on the coordination sphere of manganese (III).…”
Section: Introductionmentioning
confidence: 99%
“…Such a small effective 55 Mn hyperfine coupling parameter ( A ∥ ) has been observed previously for several 6-coordinate Mn(III) centers. 33,35,36 There has also been a preliminary report that showed a fraction of 5-coordinate Ec Mn 3+ SOD converts to a new species at pH 11.54 that is characterized by a parallel-mode EPR spectrum with A ∥ ( 55 Mn) = 3.3 mT. 31 …”
Section: Resultsmentioning
confidence: 99%